Pengaruh Work-Life Balance, Stres Kerja, dan Kepuasan Kerja terhadap Turnover Intention (Studi pada Pekerja Generasi Milenial di Yogyakarta) - Pebriana Barage; Eka Sudarusman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
Good management must have a main goal in the field of Human Resources (HR) in managing members of the company›s organization. This means that organizational actors do not have the desire to leave the company. The desire of employees to move or leave the company is called turnover intention. Turnover intention can be a problem because it will increase the cost of recruitment, selection, and training as well as disrupt the work system in the company. The factors that cause turnover intention are organizational commitment, organizational culture, job satisfaction, work environment, compensation, employee relations, work stress and work life balance. This study aims to determine the effect of work-life balance, work stresS and job satisfaction on turnover intention in the millennial generation in Yogyakarta. The sample is 100 people who are millennial generation workers who have met the criteria aged 21 to 40 years, working at least six months in Yogyakarta. Samples were taken by using non-prability sampling technique or using purposive sampling. With criteria aged 21 to 40 years, and have worked at least six months in Yogyakarta. Based on a multiple linear regression test and t test, it was found that work life balance has a negative and not significant effect, work stress has a positive and significant effect, job satisfaction has a positive and significant effect on turnover intention.